A polypropylene mesh modified with poly-ε-caprolactone nanofibers in hernia repair: large animal experiment - East, Barbora; Plencner, Martin; Kralovic, Martin; Rampichova, Michala; Sovkova, Vera; Vocetkova, Karolina; Otahal, Martin; Tonar, Zbynek; Kolinko, Yaroslav; Amler, Evzen; Hoch, Jiri (International journal of nanomedicine, 2018)
Purpose: Incisional hernia repair is an unsuccessful field of surgery, with long-term recurrence rates reaching up to 50% regardless of technique or mesh material used. Various implants and their positioning within the abdominal wall pose numerous long-term complications that are difficult to treat due to their permanent nature and the chronic foreign body reaction they trigger. Materials mimicking the 3D structure of the extracellular matrix promote cell adhesion, proliferation, migration, and differentiation. Some electrospun nanofibrous scaffolds provide a topography of a natural extracellular matrix and are cost effective to manufacture. Materials and methods: A composite scaffold that was assembled out of a standard polypropylene hernia mesh and poly-ε-caprolactone (PCL) nanofibers was tested in a large animal model (minipig), and the final scar tissue was subjected to histological and biomechanical testing to verify our in vitro results published previously. Results: We have demonstrated that a layer of PCL nanofibers leads to tissue overgrowth and the formation of a thick fibrous plate around the implant. Collagen maturation is accelerated, and the final scar is more flexible and elastic than under a standard polypropylene mesh with less pronounced shrinkage observed. However, the samples with the composite scaffold were less resistant to distracting forces than when a standard mesh was used. We believe that the adverse effects could be caused due to the material assembly, as they do not comply with our previous results. Conclusion: We believe that PCL nanofibers on their own can cause enough fibroplasia to be used as a separate material without the polypropylene base, thus avoiding potential adverse effects caused by any added substances.
Keywords: Animals; chirurgické síťky; Swine, Miniature; tkáňové podpůrné struktury; Female; Hernia; nanovlákna; ženské pohlaví; Abdominal Wall; Collagen; kolagen; miniaturní prasata; Mice; prasata; Nanofibers; myši; Herniorrhaphy; Polyesters; Materials Testing; modely nemocí na zvířatech; hernie; operace kýly; Polypropylenes; Swine; Disease Models, Animal; testování materiálů; polypropyleny; zvířata; polyestery; Tissue Scaffolds; Surgical Mesh; břišní stěna